2022
DOI: 10.3390/vetsci9080428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Inclusion of Spirulina platensis on the Reproductive Performance of Female Mink

Abstract: The objective of this study was to investigate the impact of providing Spirulina platensis (Spirulina) on reproductive performance of female mink. A total of 100 adult brown female mink (Mustela vison) were randomly and equally allocated to control group (C group), in which mink were fed basal diet and Spirulina group (Sp group), where mink received basal diet supplemented with 100 mg of Spirulina/kg of body weight. The experiment lasted 5 months, starting from 1 month prior to mating till kit weaning. Weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Feeding broilers with Spirulina as a growth enhancer improves their performance by increasing their feed conversion ratio, live body weight gain and carcass yield percentages than broilers consumed basal diet ( Samarth et al, 2002 ; Kharde et al, 2012 ). Spirulina platensis -containing diets for chickens significantly increased meat production compared to control diets (Iatrou et al, 2022) . It has also been reported that Spirulina helps with the digestion of nutrients, the absorption of minerals, and the prevention of diarrhea ( Gružauskas et al, 2004 ).…”
Section: Introductionmentioning
confidence: 92%
“…Feeding broilers with Spirulina as a growth enhancer improves their performance by increasing their feed conversion ratio, live body weight gain and carcass yield percentages than broilers consumed basal diet ( Samarth et al, 2002 ; Kharde et al, 2012 ). Spirulina platensis -containing diets for chickens significantly increased meat production compared to control diets (Iatrou et al, 2022) . It has also been reported that Spirulina helps with the digestion of nutrients, the absorption of minerals, and the prevention of diarrhea ( Gružauskas et al, 2004 ).…”
Section: Introductionmentioning
confidence: 92%
“…This finding is consistent with previous research conducted on nanny goats and doe rabbits, which also demonstrated improved litter size with Spirulina supplementation [ 60 ]. In another study, Iatrou et al [ 62 ] reported that Arthrospira -treated female mink tended to an increased whelping rate.…”
Section: Introductionmentioning
confidence: 99%
“…Spirulina platensis (SP) has been reported to be an effective dietary supplement for boosting animal reproduction [1,2]. It has a significant amount of protein, accounting for 60-70% of its dry matter, and it contains all essential amino acids, vitamins, and essential minerals and fatty acids [3,4].The inclusion of SP in the nutrition of various farm animals such as pigs, goats, cattle, chickens, and even pets, as well as its application in aquaculture, has led to enhanced production, improved health, increased fertility, and profitability [5].…”
Section: Introductionmentioning
confidence: 99%